Foreign capital, technology transfer and urban unemployment: theoretical analysis - Gupta, Kausik (1999)
We consider a three-sector Generalized Harris-Todaro model where the third sector is the foreign enclave. It is assumed to be located in the urban area and uses sector-specific foreign capital. In this model technology transfer takes place from the foreign enclave to the domestic enclave. A dynamic version of the model is considered. The long-run equilibrium and the comparative steady-state effects are analyzed in the presence of technology transfer. We get some interesting effects of reduction in the tax rate on foreign capital income on the short-run equilibrium levels of national income and urban unemployment rate under some meaningful conditions. - Reproduced.
Keywords: Technology transfer; Unemployment; Foreign investment